« Ces belles voix à la dérive » : Jules Supervielle et le désir de théâtre - Florence Davaille (Continents manuscrits)
Florence Davaille studies some features of the genesis of Bolivar : one of pieces by Jules Supervielle, played in Comédie-Française in 1936 and reproduced as an opera in 1950. The paper aims to expose the core of the following play re-writings : personification of the characters’ voice – founding gesture of creation in the ontology developed by Supervielle starting from his poetical writings. Beyond passing from one literary genre to another, Supervielle’s choice of drama writing reveals to be an ultimate stage of the "poetics of incarnation" which makes this aspect of his works important, even if it is about a theatre which is quite unknown today.